Kelp Forest Restoration in Australia - Layton, Cayne; Coleman, Melinda A.; Marzinelli, Ezequiel M.; Steinberg, Peter D.; Swearer, Stephen E.; Vergés, Adriana; Wernberg, Thomas; Johnson, Craig R. (Frontiers in Marine Science, 2020)
Kelp forests dominate the rocky coasts of temperate Australia and are the foundation of the Great Southern Reef. Much like terrestrial forests, these marine forests create complex habitat for diverse communities of flora and fauna. Kelp forests also support coastal food-webs and valuable fisheries and provide a suite of additional ecosystem services. In many regions of Australia and around the world, kelp forests are in decline due to ocean warming, overgrazing, and pollution. One potential tool in the conservation and management of these important ecosystems is habitat restoration, the science and practice of which is currently undergoing substantial expansion. We summarise the present state of Australian kelp forests and emphasise that consideration of the initial drivers of kelp decline is a critical first step in restoration. With a focus on Australian examples, we review methods, implementation and outcomes of kelp forest restoration, and discuss suitable measures of success and the estimated costs of restoration activities. We propose a workflow and decision system for kelp forest restoration that identifies alternative pathways for implementation and acknowledges that under some circumstances restoration at scale is not possible or feasible. As a case study, we then apply the Society of Ecological Restoration’s 5-star evaluation to Operation Crayweed, Australia’s primary example of kelp forest restoration. Overall, no single method of kelp forest restoration is suitable for all situations, but outcomes can be optimised by ameliorating the driver(s) of kelp decline and achieving ongoing natural recruitment of kelp. Whilst scalability of kelp forest restoration to the seascape-scale remains a considerable challenge, the present review should provide a platform for future restoration efforts. However, it is also crucial to emphasise that the challenges of restoration place a high value on preventative conservation and protection of existing kelp forest ecosystems – prevention is invariably better than cure.